Implementation of Problem Based Learning Learning Models to Improve Middle School Students' Learning Outcomes on Human Respiratory System Material - Viona Safira Fada; Aris Rudi Purnomo (INOVASIA, 2024)
This study aims to describe the implementation of learning, improving learning outcomes, and student responses to problem-based learning. The type of research used is the pre-experimental design, with the research design used is "one group pretest-posttest design". Data collection was carried out using test methods in the form of pretest and posttest. The research instruments used included implementation observation sheets, pretest and posttest sheets, and student response questionnaire sheets. The results of the analysis of the implementation of learning show that the implementation of learning is running effectively, the N-Gain test has obtained a score in the high category, the student's response shows a very good category. Based on the output "Unpaired t-test" is <0.05. Shows the influence of problem-based learning on student learning outcomes. Thus, the application of problem-based learning is effectively applied in the learning process.